ISLAM DAN POLITIK PEMERINTAHAN (Pemikiran Politik Muhammad Husein Haikal) - Kesuma, Arsyad Sobby (Analisis: Jurnal Studi Keislaman, 2013)
Discussing   themes or concepts  of Islamic   government   system seems to be an endles activity as a great number of books  written by muslim intellectuals  from  time to time  continously   appear. the present  day.   This paper tries to explore ideas and political thought of one Muslim intellectual  , Muhammad Husayn Haykal. After a thorough scrutinization to his works,  this  study finds out that his conception of political thought was based on the Oneness of Allah (Tauhidiyah).   In addition, he also identified three basic principles of humanism upon which Islamic state should be based, namely : the principles of human brotherhood,  of human equality, and of human freedom. Haykal also asserted  that   the   form of constitutional state is preferable  as compared to others .